Internationalization strategies of multi-product firms: The role of technology - Daniel Baumgarten; Michael Irlacher; Karin Mayr (Johannes Kepler University of Linz, Department of Economics, 2020)
High-performance firms typically have two features in common: i) they produce in more than one country and ii) they produce more than one product. In this paper, we analyze the internationalization strategies of multi-product firms at the product-level. We find that the most productive firms sell core varieties via foreign direct investment (FDI) and export products with intermediate productivity. Shocks to trade costs and technology affect the endogenous decision to export or produce abroad at the product-level and, in turn, the relative productivity between parents and affiliates.
Keywords: F12; F23; L25; L11; 330; Multi-product firms; FDI; exports; flexible manufacturing